Legionella pneumophila — The causative agent of Legionnaires’ disease - Loh Teng-Hern Tan; Wei Yu Tee; Tahir Mehmood Khan; Long Chiau Ming; Vengadesh Letchumanan (Progress in Microbes and Molecular Biology)
Over the years, Legionella pneumophila has increasingly become a public health threat that causes sporadic and epidemic community-acquired and nosocomial-acquired pneumonia. Thus, this review aims to discuss the current knowledge of L. pneumophila, focusing on the global epidemiology, clinical features, diagnosis and treatment of Legionnaires’ disease (LD). Legionella bacteria are Gram-negative rod-shaped bacteria that are ubiquitous in aquatic environments. L. pneumophila was first discovered in 1976 and recognized as the causative agent of LD. L. pneumophila is a facultative intracellular pathogen that infects and replicates within eukaryotic host cells such as macrophages and protozoan. Diagnosis of LD remains a significant challenge as the clinical manifestation of LD is hardly distinguishable from pneumonia caused by other respiratory pathogens. Therefore, early testing and appropriate treatment are keys to alleviating the rising morbidity and mortality caused by LD.